(untitled) (Research Nepal Journal of Development Studies, 2022)
The globe is said to be patriarchal so it has created the identity of women that is based on their marriage. How does marriage create an identity for women? The objective of the study is to examine the perception of people towards marriage, women’s identity, and its connection. It is analyzing the connection between women’s identity and marriage and explores the women’s identity. It is a qualitative case study of four women. The method of study was qualitative as researchers had selected four married women purposively and then took face-to-face interviews mainly focusing on the objective. After that researchers transcribed those recorded qualitative data and analyzed them. The researchers again consult with respondents to maintain the validity and reliability of the data. In conclusion, people’s perception in society is that the identity of the woman is always linked with her marital status after reaching certain age prescribed by society as the age to get married. It means there is a very close relation between marital status and the identity of women because of the male-dominated culture of the world. A male-dominated culture brings much psychological and social torture to the women who want to create their own identity in the world.